2019
DOI: 10.1111/1440-1681.13123
|View full text |Cite
|
Sign up to set email alerts
|

MLK3 silence induces cervical cancer cell apoptosis via the Notch‐1/autophagy network

Abstract: Mixed‐lineage kinase 3 (MLK3), the mitogen‐activated protein kinase kinase kinase (MAP3K), has been recognized as a player in tumorigenesis and oncogenic signalling, yet its detailed functions and signalling in cervical cancer have not been fully elucidated. Here, we identify that cervical cancer cells display higher mRNA and protein levels of MLK3 than normal cervical epithelial squamous cells. In HeLa and SiHa cell, MLK3 knockdown using siRNA remarkably suppressed cell survival and promoted cell apoptosis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In the cervical cancer microenvironment, many kinds of different moleculars mediate the mutual impact of autophagy and apoptosis. Liya Ma et al performed a study demonstrated that the silence of MLK3 induces the apoptosis of CC cells via the Notch-1/autophagy network [46]. An experiment performed by Liu S et al…”
Section: Discussionmentioning
confidence: 99%
“…In the cervical cancer microenvironment, many kinds of different moleculars mediate the mutual impact of autophagy and apoptosis. Liya Ma et al performed a study demonstrated that the silence of MLK3 induces the apoptosis of CC cells via the Notch-1/autophagy network [46]. An experiment performed by Liu S et al…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer MLK3 (MAP3K11) also facilitates the collagen type I-induced EMT switch, leading to JNK-mediated increased expression of N-cadherin, an EMT marker associated with promoting migratory and invasive capacity [103,104]. Ma et al [105] showed that MLK3 expression is upregulated in cervical cancer cells and MLK3 blocking suppresses cancer progression via autophagy-dependent apoptosis. Additionally, targeting MAP3K11 using microRNA inhibited tumor proliferation in NSCLC and esophageal cancer [106,107].…”
Section: Map3k11mentioning
confidence: 99%
“…7 Cervical cancer (CC) is a malignancy threatening women's reproductive health. 8 So far, a lot of studies have proved that aberrant mRNAs influence CC progression, 9,10 like cell cycle, 11 cell apoptosis, 12 glycolysis, 13 cell autophagy, 14 and epithelial-mesenchymal transition. 15 Therefore, understanding the function of mRNAs in CC progression is of great importance to CC treatment.…”
Section: Introductionmentioning
confidence: 99%